2012
DOI: 10.1021/ma302192b
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Surface Mechanical Properties of Poly(α-methylstyrene): Surface Softening and Stiffening at Different Temperatures

Abstract: We report results from experiments based on the spontaneous particle embedment technique to determine the surface compliance of poly(α-methylstyrene) (PαMS) for temperatures from room temperature to T g + 21 °C. Both submicrometer and nanometer diameter particles were investigated. Atomic force microscopy (AFM) measurements were used for the particle embedment determination, and the Lee and Radok (LR) model was applied to calculate the surface shear compliances using the embedment depth of the particles for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 60 publications
3
18
0
Order By: Relevance
“…By using nanobubble inflation to measure creep compliance of free‐standing poly(vinyl acetate) and polystyrene films in the rubbery regime, O'Connell and McKenna revealed a stiffening of modulus with decreasing thickness for sub‐200 nm films . Karim and McKenna later used nanoparticle embedding techniques to measure stiffness at the free surface in poly(α‐methylstyrene) (PαMS) . They noted a softening of the surface well into the glassy state, consistent with previously mentioned confined polymer studies .…”
Section: Confined Polymer Propertiessupporting
confidence: 68%
See 2 more Smart Citations
“…By using nanobubble inflation to measure creep compliance of free‐standing poly(vinyl acetate) and polystyrene films in the rubbery regime, O'Connell and McKenna revealed a stiffening of modulus with decreasing thickness for sub‐200 nm films . Karim and McKenna later used nanoparticle embedding techniques to measure stiffness at the free surface in poly(α‐methylstyrene) (PαMS) . They noted a softening of the surface well into the glassy state, consistent with previously mentioned confined polymer studies .…”
Section: Confined Polymer Propertiessupporting
confidence: 68%
“…Several techniques have been developed to measure the mechanical properties of ultrathin polymer films and have largely been used to elucidate deviations from bulk stiffness and residual stress . The experimental temperatures at which these studies were performed proved important in revealing different confinement behaviors below and above bulk T g : glassy softening and rubbery stiffening .…”
Section: Confined Polymer Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar observations of an indentation depth dependent modulus have been observed by other groups in experiments on amorphous glassy polymers, where it has been reported that the mechanical response at small scales can be different from those of the macroscopic material. In those cases the surface has been reported to be different from the bulk, i.e., softer or stiffer , and sometimes the same. A full understanding remains elusive, though it seems that the pressure dependence of the glass transition temperature is important .…”
Section: Resultsmentioning
confidence: 99%
“…In those cases the surface has been reported to be different from the bulk, i.e., softer or stiffer , and sometimes the same. A full understanding remains elusive, though it seems that the pressure dependence of the glass transition temperature is important .…”
Section: Resultsmentioning
confidence: 99%